Ang tao sa kwadro - Medina, Buenaventura S. 4 0 16; 5 (Manila, Philippines : De La Salle University Press, 1996)
Criticism on essays, language, and literature of the Philippines.
Includes bibliographical references.
In Tagalog.
Keywords: 2 -- 0; 6; History and criticism.;History and criticism. -- Philippine literature;Tagalog literature -- 20th century;20th century20; 20; 2